2020
DOI: 10.1002/jcp.29830
|View full text |Cite
|
Sign up to set email alerts
|

Computational and in vitro characterization of ICY‐5: A potential candidate promoting mitochondrial apoptosis via the c‐MET and STAT3 pathways

Abstract: Targeted chemotherapy remains the primary choice in controlling various forms of breast cancer (BC) due to its heterogenous gene expressions in various subtypes. In silico and in vitro evaluation of ICY-5, a novel arylidene analogue against c-MET, was performed. ICY-5 exhibited a docking score of −9.6 kcal/mol in inactive conformation and, − 8.6 kcal/mol in active conformation for c-MET. ICY-5 inhibited c-MET enzyme with an IC 50 of 34.34 nM. The compound effectively inhibited MDA-MB 231 and MCF-7 cell prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…All three AML cells were treated with different doses of SSB-2548 along with DMSO controls and incubation for 48 h. Apoptosis was analyzed by using Annexin V detection kit as described elsewhere [22]. Percentage of early and late phase apoptotic populations in comparison to respective controls were presented.…”
Section: Apoptosis Detection Assaymentioning
confidence: 99%
“…All three AML cells were treated with different doses of SSB-2548 along with DMSO controls and incubation for 48 h. Apoptosis was analyzed by using Annexin V detection kit as described elsewhere [22]. Percentage of early and late phase apoptotic populations in comparison to respective controls were presented.…”
Section: Apoptosis Detection Assaymentioning
confidence: 99%
“…Apoptosis refers to the active and orderly death of cells that maintains homeostasis of the internal environment under physiological or pathological conditions ( 17 , 18 ). Exposure of cells to internal pro-apoptotic factors, such as activators of oncogenes, agents that cause DNA damage, cell hypoxia, and deficiency of cell growth factors, has been revealed to activate apoptosis of mitochondrial cells ( 19 ). Previous studies have demonstrated that dysregulation of apoptosis can result in a variety of human diseases, including development and regression of tumors ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%